1991
DOI: 10.5271/sjweh.1726
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and bedding materials as sources of microbial exposure on dairy farms.

Abstract: KOTIMAA MH, OKSANEN L, KOSKELA P . Feeding and bedding materials as sources of microbial exposure on dairy farms. ScandJ WorkEnvironHealth 1991:17:117-22. Hay, grain, silage, and bedding are the sources of mold dust in agriculture. The aim of the present study was to evaluate the effect of different farming methods on exposure to airborne microbes. The study material comprised 50 silage, 54 hay, 47 grain , and 70 beddin g samples taken on 18 farm s in the beginning , middle, and end of the indoor feeding se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…The chosen exposure indicator, animal production, represents daily exposure to antigens, allergens, particles from animals, and microorganisms in fodder and bedding materials (4,6,38,39). The relevance of the many different exposure factors for airway disease are not known (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chosen exposure indicator, animal production, represents daily exposure to antigens, allergens, particles from animals, and microorganisms in fodder and bedding materials (4,6,38,39). The relevance of the many different exposure factors for airway disease are not known (7).…”
Section: Discussionmentioning
confidence: 99%
“…Immunologically potent substances such as antigens, allergens, endotoxins, glucans, and substances with complement-stimulating and adjuvant effects have been identified in agricultural dust of different origins (4)(5)(6). The inhalation of agricultural dust provoltes inflammatory reactions in the airways (5,7).…”
Section: O F L~l I I~i~f L Smentioning
confidence: 99%
“…To determine the relative survival (RS), the test sampler was placed under the flow straightener in the test chamber together with the rcference sampler, with the AGI-30 impinger sct at a flow rate of 12.5 Llmin, which was widely applied in field measurement. During the tests the concentrations measured by APS ranged from lo4 to lo8 partieles1m3, which represented the medially to highly contaminated environments (Malmberg et al, 1988;Rahkonen et al, 1990;Kotimaa et al, 1991;Rautiala et al, 1996;van der Werf, 1996;Nielsen et al, 1997). By controlling the amounts of harvested spores and the volume of the speaker, the concentrations could be maintained around 10\articles/m"or at last three hours.…”
Section: Test Systemmentioning
confidence: 99%
“…Fungal spores originate from different sources in the agricultural environment. Laboratory and experimental studies have indicated that the same fungal species that are identified in hay, grain, straw, silage, wood shavings, and sawdust are also detected in the air samples collected during the handling of the same materials (6,(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%